Penyuluhan tentang perilaku hidup bersih dan sehat bagi siswa-siswi di SMA Negeri 1 Sapuran, Wonosobo, Jawa Tengah - Florentina Kusyanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
There were some students that spit their saliva out of the windows and spit their saliva outwhen they were in the classroom. There were also some teachers who were smoking in inappropriate place and some students who were throwing rubbish, such as candies wrap, anywhere. Teachers and students were still having low concern in maintaining the toilet and shower, hence the toilet and shower were still smelly and dirty. This activity was intended to implement “tri dharma perguruan tinggi” and to share the knowledge to other people, especially for students of SMA Negeri 1 Sapuran, Wonosobo. Hopefully, at the end of this activity, the students would realize the importance of implementing program called Perilaku Hidup Bersih dan Sehat (PHBS) or Healthy and Clean Behavior in the School. This community empowerment was carried out in one day in July 2016, in SMA Negeri 1 Sapuran, Wonosobo, Central Java. In this community empowerment, there is no pre-test, but two months of observation have been carried out after the activity. The method that used for health education is counseling. Students are collected in the hall then given material through Microsoft PowerPoint software with lectures, questions, and answers thenfollowed by a post-test to find out whether the material provided is useful in increasing the knowledge and application of Healthy and Clean Behavior for students. From the results of observations on 159 students, it is known that their knowledge is good. The post-test results showed that 81.8% of students had good knowledge. The application of Healthy and Clean Behavior during the observation period in two months after counseling was good, not much rubbish was scattered in the yard.